Parental exposure of Eastern oysters ( Crassostrea virginica ) to elevated p CO 2 mitigates its negative effects on early larval shell growth and morphology - Elise M. McNally; Alan M. Downey‐Wall; F. Dylan Titmuss; Camila Cortina; Kathleen Lotterhos; Justin B. Ries (Limnology and Oceanography, 2022)
Larvae of marine calcifying organisms are particularly vulnerable to the adverse effects of elevated p CO 2 on shell formation because of their rapid calcification rates, reduced capacity to isolate calcifying fluid from seawater, and use of more soluble polymorphs of calcium carbonate. However, parental exposure to elevated p CO 2 could benefit larval shell formation through transgenerational plastic responses. We examined the capacity of intergenerational exposure to mitigate the adverse effects of elevated p CO 2 on Eastern oyster ( Crassostrea virginica ) early larval shell growth, shell morphology, and survival. Adult oysters were exposed to control (572 ppm p CO 2 ) or elevated p CO 2 (2827 ppm p CO 2 ) conditions for 30 d during reproductive conditioning. Offspring from each parental treatment were produced using a partial North Carolina II cross design and grown under control and elevated p CO 2 conditions for 3 d. We found evidence of transgenerational plasticity in early larval shell growth and morphology, but not in survival, in response to the parental p CO 2 exposure. Larvae from parents exposed to elevated p CO 2 exhibited faster shell growth rates than larvae from control parents, with this effect being significantly larger when larvae were grown under elevated p CO 2 compared to control conditions. Parental exposure to elevated p CO 2 , however, was insufficient to completely counteract the adverse effects of the prescribed elevated p CO 2 on early larval shell formation and survival. Nevertheless, these results suggest that oysters have some capacity to acclimate intergenerationally to ocean acidification.